The prevalence of menstrual cycle disorders and menstrual cycle-related symptoms in female athletes: a systematic literature review - Taim, B. C.; Ó Catháin, C.; Renard, M.; Elliott-Sale, K. J.; Madigan, S.; Chéilleachair, N. N. (Sports Medicine, 2023)
Background: Menstrual cycle (MC) disorders and MC-related symptoms can have debilitating effects on the health and performance of female athletes. As the participation of women in sports continues to increase, understanding the prevalence of a range of MC disorders and MC-related symptoms may guide preventive strategies to protect the health and optimise the performance of female athletes. Objective: To examine the prevalence of MC disorders and MC-related symptoms among female athletes who are not using hormonal contraceptives and evaluate the assessment methods used to identify MC disorders and MC-related symptoms. Methods: This systematic review was performed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Six databases were searched until September 2022 for all original research that reported the prevalence of MC disorders and/or MC-related symptoms in athletes not using hormonal contraceptives, which included the definitions of the MC disorders examined, and the assessment methods used. MC disorders included amenorrhoea, anovulation, dysmenorrhoea, heavy menstrual bleeding (HMB), luteal phase deficiency (LPD), oligomenorrhoea, premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD). MC-related symptoms included any affective and physical symptoms related to the MC that do not cause significant personal, interpersonal or functional impairment. The prevalence data across eligible studies were combined, and all studies were qualitatively synthesised to evaluate the assessment methods and tools used to identify MC disorders and MC-related symptoms. The methodological quality of studies was assessed using a modified Downs and Black checklist. Results: Sixty studies involving 6380 athletes were included. A wide range of prevalence was observed for all types of MC disorders, with a dearth of data on anovulation and LPD. Based on pooled data, dysmenorrhoea (32.3%; range 7.8-85.6%) was the most prevalent MC disorder. Studies reporting MC-related symptoms mostly examined the premenstrual and menstruation phases, where affective symptoms appeared more prevalent than physical symptoms. A larger proportion of athletes reported symptoms during the initial days of menstruation compared with the premenstrual phase. MC disorders and MC-related symptoms were retrospectively assessed using self-report methods in 90.0% of studies. Most studies (76.7%) in this review were graded as moderate quality. Discussion: MC disorders and MC-related symptoms are commonplace among female athletes, warranting further research examining their impact on performance and preventive/management strategies to optimise athlete health. To increase the quality of future studies, researchers should adopt standardised definitions of MC disorders and assessment methods such as a combination of calendar counting, urinary ovulation tests and a mid-luteal phase serum progesterone measurement when assessing menstrual function. Similarly, standardised diagnostic criteria should be used when examining MC disorders such as HMB, PMS and PMDD. Practically, implementing prospective cycle monitoring that includes ovulation testing, mid-luteal blood sampling (where feasible) and symptom logging throughout the MC could support athletes and practitioners to promptly identify and manage MC disorders and/or MC-related symptoms.